An audit of health student immunisation at a University Department of Rural Health reveals the imperative for a coordinated approach - Caroline Crossley; Sandra Thompson (Elsevier, 2021)
Abstract Objective: Student healthcare worker immunisation ensures the protection of students, their patients and the wider community. This audit assessed allied health students' records of immunisation against national standards. Methods: This audit examined clinical students' immunisation records at a University Department of Rural Health and assessed their compliance with the national Australian Immunisation Handbook recommendations. Gaps in processes were assessed through a review of forms, guidelines and stakeholder feedback. Results: Around one‐quarter (26%) of healthcare students provided evidence that they were immunised in line with national standards. Inconsistency of immunisation recommendations across universities, states and disciplines were identified. Conclusions: This audit highlighted gaps in healthcare student immunisation assurance processes at both local and national levels, and we recommend key elements that would be required for a more consistent, streamlined and coordinated approach. Implications for public health: As a pillar of communicable disease control, immunisation compliance continues to pose important public health challenges. Without further work towards coordination of healthcare students' immunisation assurances, there is a risk of preventable morbidity and mortality in vulnerable communities, as well as suboptimal student and worker safety in an environment that poses high risks.